1981
DOI: 10.1080/09670878109413826
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Basal Rot of Onion in Zambia

Abstract: In a commercial planting of onion, root and basal rots reduced establishment of sets to 44%. which with 30% basal rot in harvested bulbs, represented an overall numerical loss of potential yield of 69%. Fusarium oxysporum, already present in sets at planting, contributed to poor establishment. Isolation from seedlings grown for sets in virgin soil at three locations yielded infection rates of 80 to 90%. In two field trials to evaluate fungicide treatments mean establishment was 47%. In the f i r s t trial invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Pre-planting dipping of onion bulbs with benomyl (100 μg.mL −1 for 15 min.) reduced basal rot by 65% and enhanced yield with 54% (Naik and Burden 1981). Similar results were obtained when combined with vinclozolin (Özer and Ömeroğlu 1995) or mancozeb (Naik and Burden 1981).…”
Section: Chemical Controlsupporting
confidence: 72%
See 2 more Smart Citations
“…Pre-planting dipping of onion bulbs with benomyl (100 μg.mL −1 for 15 min.) reduced basal rot by 65% and enhanced yield with 54% (Naik and Burden 1981). Similar results were obtained when combined with vinclozolin (Özer and Ömeroğlu 1995) or mancozeb (Naik and Burden 1981).…”
Section: Chemical Controlsupporting
confidence: 72%
“…Even when cultivated in virgin soil, the presence of FBR is quite high as observed in Zambia, where 80-90% of the transplants were infected by F. oxysporum f. sp. cepa, resulting in enormous losses in post-transplanting seedlings (44%) and potential yield (69%) (Naik and Burden 1981). The level of losses is usually higher in organic farms than in conventional farms (Haapalainen et al 2016).…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of Granosan 200 (benomyl 15% + mancozeb 60%) declined this disease by 77%, consequently onion yield was increased by 106% (Naik and Burden, 1981). Recently, Behrani et al (2015) found carbendazim and antracol very effective in controlling basal rot of onion.…”
Section: Introductionmentioning
confidence: 99%
“…F. oxysporum f. sp. cepae reduces seed yield, germinability, 1000 seed weight (Barnoczki-Stoilova, 1986) and generally kills young seedling at pre-and post-emergence stages (Naik and Burden, 1981;Kodama, 1983;Srivastava and Qadri, 1984;Özer and Köycü, 1997). Symptoms on set bulbs are difficult to observe.…”
Section: Symptoms and Epidemiologymentioning
confidence: 99%